Mapping Kappa Opioid Receptor Binding in Titi Monkeys with [C]GR103545 PET - Alita Jesal D Almeida BEng; Brad A. Hobson PhD; Logan E. Savidge PhD; Claudia Manca BS; John P. Paulus BS; Karen L. Bales PhD; Abhijit J. Chaudhari PhD (Molecular Imaging)
Purpose The kappa opioid receptor (KOR) plays a pivotal role in stress- and anxiety-related behaviors, with growing evidence linking it to stress induced by social isolation and separation. Despite this, tools for studying KOR in clinically relevant social contexts remain limited. The socially monogamous coppery titi monkey offers a translational model for investigating pair bonding. This study evaluated the feasibility of [ 11 C]GR103545 PET imaging to characterize KOR activity in vivo , and its pharmacological blockade for the first time in titi monkeys. Methods Adult titi monkeys (N = 6) underwent [ 11 C]GR103545 PET brain scans at baseline and following administration of the KOR antagonist CERC-501. Non-displaceable binding potential (BP ND ) was calculated across 14 brain volumes of interest (VOIs) implicated in social bonding, using Simplified and Logan reference tissue models (SRTM and LRTM), with the cerebellum as the reference region. Results Baseline [ 11 C]GR103545 uptake patterns across VOIs were consistent with reports in humans, other primates and published autoradiography data. CERC-501 pretreatment significantly reduced BP ND (SRTM: 55.99%, LRTM: 59.68%) across several, but not all brain VOIs. Conclusions This study establishes [ 11 C]GR103545 PET as a viable tool for assessing KOR binding dynamics in titi monkeys, providing new opportunities to explore KOR modulation in social bonding and separation.